2013
DOI: 10.3233/ies-130488
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of measurements of lower-limb muscle strength obtained with a hand-held dynamometer from patients with stroke

Abstract: BACKGROUND: The responsiveness of measurements obtained by hand-held dynamometry (HHD) is largely unexplored. OBJECTIVE: A secondary analysis of data from a clinical cohort of patients (N = 55) admitted for inpatient rehabilitation following acute stroke was completed to determine the responsiveness of measures of lower extremity muscle strength. METHOD:The isometric strength of hip flexion, knee extension, and ankle dorsiflexion was measured bilaterally in 55 patients using HHD. Independence in bed-to-chair t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…The examined muscle groups of the lower limbs (i.e. hip flexors, knee flexors, knee extensors and ankle dorsiflexors), measured within the early subacute stage, showed a significant increase in muscle strength on the paretic side with moderate, positive effect sizes (p < 0.05, g H : 0.34-0.70) (31,34,62,63).…”
Section: Muscle Strengthmentioning
confidence: 97%
See 4 more Smart Citations
“…The examined muscle groups of the lower limbs (i.e. hip flexors, knee flexors, knee extensors and ankle dorsiflexors), measured within the early subacute stage, showed a significant increase in muscle strength on the paretic side with moderate, positive effect sizes (p < 0.05, g H : 0.34-0.70) (31,34,62,63).…”
Section: Muscle Strengthmentioning
confidence: 97%
“…Concerning the non-paretic side, muscle strength of the lower limbs significantly increased in the hip flexors (p < 0.05, g H : 0.24-0.25) and ankle dorsiflexors (p < 0.05, g H : 0.26-0.31) (31,34), whilst studies that investigated the knee extensors and flexors reported mixed results (p < 0.001 to p > 0.05, g H : 0.06-0.28) (31,34,49,62,63).…”
Section: Muscle Strengthmentioning
confidence: 99%
See 3 more Smart Citations